Letter (copy) : Spanish refugees - Citrine, Walter, 1887-1983
042-0147-001 WMC/WJB/AC/706 International 6th May, 1937. Dr. Fritz Riesenfeld, Widdlecombe, Pump Lane, Rainham, KENT. Substitute Dear Sir, SPANISH REFUGEES. We are in receipt of your letter of 5th instant, and are much obliged to you for the offer of the services of yourself and your colleague on behalf of Spanish refugees in England. The great majority of the refugees with whom our International is concerned are living in France, but we will keep your kind offer in mind so as to make use of it when the opportunity arises. Yours faithfully, General Secretary. 292/946/42/147